2021
DOI: 10.1080/2331186x.2021.1948660
|View full text |Cite
|
Sign up to set email alerts
|

Do entrepreneurship education and environment promote students’ entrepreneurial intention? the role of entrepreneurial attitude

Abstract: Entrepreneurial intention plays a central role in stimulating the growth of entrepreneurs. The purpose of this investigation is to explore the relationship between several forecasted variables that can drive to students' entrepreneurial intention, consisting of entrepreneurial education, entrepreneurial attitude, family education, and environment. We applied a quantitative approach with a cross-sectional survey model to capture the digestion of how entrepreneurship education, family education, environment, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 62 publications
0
34
0
1
Order By: Relevance
“…Besides, the intervention also indirectly improved academic and professional interest through entrepreneurial self-efficacy. Kusumojanto et al (2021) adopted a quantitative method with a cross-sectional survey model to understand how entrepreneurship education, family education, environment, and entrepreneurial attitude explain vocational students’ entrepreneurial intention. The scholars took vocational students in Malang, Indonesia as a sample for analysis by using the model structure and iterative theory of the structural equation modeling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, the intervention also indirectly improved academic and professional interest through entrepreneurial self-efficacy. Kusumojanto et al (2021) adopted a quantitative method with a cross-sectional survey model to understand how entrepreneurship education, family education, environment, and entrepreneurial attitude explain vocational students’ entrepreneurial intention. The scholars took vocational students in Malang, Indonesia as a sample for analysis by using the model structure and iterative theory of the structural equation modeling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jena (2020) added that entrepreneurial intention is proxied by the primary factors, including individual characteristics and the environment, while Pauceanu et al (2019) revealed that entrepreneurial confidence impacts students' entrepreneurial intention. The recent studies in the Indonesian context believe that the low level of intention of entrepreneurs can be predicted by cultural and entrepreneurial attitude (Wardana et al, 2021), mindset and knowledge (Karyaningsih et al, 2020), entrepreneurial environment (Kusumojanto et al, 2021).…”
Section: Public Interest Statementmentioning
confidence: 99%
“…Meanwhile, Patricia and Silangen (2016) focused on the nexus between entrepreneurial education and the intention of being entrepreneurs. Lastly, Indarti (2004); Kusumojanto et al (2021) mentioned that entrepreneurial intention among Indonesia is determined by self-efficacy, while other factors, such as locus of control and demographic do not influence university students' intention towards entrepreneurship.…”
Section: Public Interest Statementmentioning
confidence: 99%
See 2 more Smart Citations